Digging deep into diabetes: achieving better glycemic control in diabetic patients in a resident-run clinic - Sara Hawatmeh; Maggie Meier; Erika Leung; Ramza Haque; Harinderjeet Kaur; Muhammad F. Asghar; Amirsoheil Talebian; Osman Qaiyum; Rajat Shailly; Omar Al-Abboud; Keerthi Patlolla; Akm Towfique Aziz; et al. (Greater Baltimore Medical Center, 2019)
Background: Diabetes mellitus (DM) affects over 30 million Americans with an estimated annual cost of $327 billion in 2017. Patients with diabetes, especially with financial and/or social hardships, pose challenges in achieving target hemoglobin A1c (HbA1c) values. Understanding patient-specific barriers offer opportunities to improve outcomes in patient care. Objective: We aimed to improve a patient's glycemic control by reducing barriers to care. Furthermore, we evaluated the impact that a resident quality improvement effort had on providing high value diabetic care. Methods: We performed a retrospective cohort study of patients with HbA1c >9.0% in an underserved, resident-run clinic. Patients were surveyed on their knowledge of diabetes and reported obstacles to achieve diabetic control. We then implemented a 12 -month customized, patient-directed, multi-modal, multidisciplinary intervention. Results: Ninety-four patients with HbA1c >9.0% were identified, 65 surveyed, and 51 included in the intervention phase. After the intervention phase, re-evaluation of HbA1c in a paired sample comparison showed that the average HbA1c had decreased by 1.41% (11.28% vs. 9.87%, p < 0.01). Among the patients included in the intervention group, approximately 8% had their HbA1c reduced by ≥50% from their baseline, 23% had their HbA1c reduced by ≥25% from their baseline and 49% had their HbA1c reduced by ≥10% from their baseline. Conclusions: A strategically designed, a patient-centered customized intervention can have a positive impact on a patient's diabetic control.